Power Increasing Sequences and Their Some New Applications - Hüseyin Bor (Abstract and Applied Analysis)
In the work of Bor (2008), we have proved a result dealing with summability factors by using a quasi--power increasing sequence. In this paper, we prove that result under less and more weaker conditions. Some new results have also been obtained.